Teacher Training in the Education Sector of Universidade Federal do Paraná (1938-2010) - Carlos Eduardo Vieira; Nadia Gaiofatto Gonçalves (Universidade Federal do Rio Grande do Sul, 2016)
This article is intended to convey the history of the process of teacher training at the higher education level in Paraná state. The conducting thread of the analysis are aspects related to the creation of the first higher education institution in the state, known since 1950 as Universidade Federal do Paraná (UFPR). We will emphasize the changes in the institutional, political and curricular configurations associated with the different academic aspects involved in the teacher training processes at UFPR between 1938 and 2010. Special attention will be dedicated to the implementation and consolidation of the pedagogy course and the Education Sector, and we will analyze proposals and actions related to the teacher training courses at the institution.